Keterampilan proses sains dalam konteks project praktikum sederhana berbasis etnokimia: Sebuah telaah literatur - Abu, St Hayatun Nur; Rahman, Nurul Aulia; Mauraji, Ilham S. W (Arfak Chem: Chemistry Education Journal, 2025)
Science process skills are essential aspects of learning aimed at shaping students capable of thinking critically and analytically and applying scientific concepts in real-life situations. However, various studies have shown that these skills remain moderate to low in Indonesia. This condition is attributed to learning approaches that are still theoretical, limited laboratory activities, and inadequate lab facilities. A contextual and practical learning strategy is needed to address these challenges, one of which is through simple project-based practicums integrated with ethnochemistry. Ethnochemistry, a branch of ethnoscience, enhances students’ motivation to learn chemistry and deepens their understanding of local culture. This study employs a literature review method involving eight national and international journal articles. The results indicate that this approach is practical in developing science process skills. Simple project-based learning incorporating local values through ethnochemistry presents a promising alternative to improving the quality of science education in schools.